Pengaruh Teknologi Dan Media Sosial Terhadap Perubahan Perilaku Remaja - Nurul Desy Saputri (LPPM Politeknik Pratama, 2024)
Adolescent development is considered rapid in all aspects. And technology will always be related to teenagers' lives. Not only at school, at home teenagers are also equipped with technology. In technology there is social media. The use of social media is considered a relevant and appropriate communication strategy for teenagers. This research uses a qualitative descriptive method in the form of library research. The aim of this research is to determine the influence of technology and social media on the development of adolescent behavior.Technology and social media have a big influence on the development of adolescent behavior. The resulting influence is both good and bad.